2011
DOI: 10.1007/s10705-011-9433-5
|View full text |Cite
|
Sign up to set email alerts
|

Fate of labeled urea-15N as basal and topdressing applications in an irrigated wheat–maize rotation system in North China Plain: I winter wheat

Abstract: A field micro-plot experiment for winter wheat was conducted in an irrigated winter wheat (Triticum aestivum)-summer maize (Zea mays L.) rotation system in Mazhuang, Xinji of Hebei province in the North China Plain, using the 15 N isotope method to determine the effects of N application (rates and timing), and irrigation frequency on urea-15 N fate, residual-N and N recovery efficiency (NRE) of wheat. The experiment was conducted under two irrigation treatments (I2 and I3, representing for two and three irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 17 publications
6
24
1
Order By: Relevance
“…3). In particular, 68% of basal applied N remained in the soil and this ratio exceeded that for topdressing of N. This result is well supported by Jia et al (2011), who reported that 37-51% of the basal applied N remained in the soil on harvest and the ratio exceeded that from topdressed N. Stevens et al (2005) reported that 20-55% of inorganic 15 N was converted into an immovable form, including organic and clay-fixed forms, during the maize growing season. Sugihara et al (2010) studied the effect of rainfall after the dry period on microbial biomass and N dynamics and revealed increasing microbial biomass and a drastic decline in inorganic N after rewetting by rainfall, which occurred within 50 hours of rainfall.…”
Section: Fate Of N Unabsorbed By Sweet Sorghumsupporting
confidence: 57%
See 2 more Smart Citations
“…3). In particular, 68% of basal applied N remained in the soil and this ratio exceeded that for topdressing of N. This result is well supported by Jia et al (2011), who reported that 37-51% of the basal applied N remained in the soil on harvest and the ratio exceeded that from topdressed N. Stevens et al (2005) reported that 20-55% of inorganic 15 N was converted into an immovable form, including organic and clay-fixed forms, during the maize growing season. Sugihara et al (2010) studied the effect of rainfall after the dry period on microbial biomass and N dynamics and revealed increasing microbial biomass and a drastic decline in inorganic N after rewetting by rainfall, which occurred within 50 hours of rainfall.…”
Section: Fate Of N Unabsorbed By Sweet Sorghumsupporting
confidence: 57%
“…NREisotopic was reportedly higher in topdress-15 N than in basal-15 N for wheat (Triticum aestivum L.) (Jia et al 2011) and maize (Zea mays L.) (Yang et al 2011). In the present study, NREisotopic was markedly lower in basal N application than in topdressings (Fig.…”
Section: Fate Of N Absorbed By Sweet Sorghumsupporting
confidence: 47%
See 1 more Smart Citation
“…Ju et al (2007) found that 29-50% of the applied N remained in soil after the first crop harvest, and less than 7.5% of the applied N was uptaken by the second crop in a winter wheat (Triticum aestivum L.) and summer maize (Zea mays L.) rotation system in North China Plain. Jia et al (2011) observed recovery of residual N by the second and third crops in a winter wheat-summer maize rotation under different N application rates and times, and irrigation frequency of 5-10% and 1.7-3.5%, respectively. Another study reported that crops used on average only 3% of the N surplus within 3 years under slurry and inorganic N fertilizer treatments near Kiel in northwest Germany (Sieling et al 2006).…”
Section: Introductionmentioning
confidence: 87%
“…Many nitrogen-15 ( that more than one third of the fertilizer N resides in soil after crop harvest (Glendining et al 1997;Macdonald et al 2002;Dang et al 2003;Ju et al 2007;Ju et al 2009;Jia et al 2011;Petersen et al 2012). The N fertilizer application rate in developed countries has decreased in recent years due to awareness of the problems of its over-use, and the implementation of different policies to alleviate the problems (Schröder and Neeteson 2008;Sutton et al 2011); however, due to more concern over food security, N fertilizer application in most developing countries is still increasing, especially in China and India (Pilbeam et al 2002;Chen et al 2011;Fan et al 2012).…”
Section: Introductionmentioning
confidence: 99%